“This is me!”: Creative digital storytelling with teacher–student and AI collaboration - Ahmad, Julianah; Sharif, Sabariah; Talin, Rosy (Jurnal Pendidikan Bitara UPSI, 2025)
Deaf students often face significant challenges in language learning, resulting in reading literacy levels that consistently lag behind those of their hearing peers, creating barriers to quality education. To address this issue, this study implemented a digital storytelling project in which teachers and deaf students collaboratively crafted storybooks that are deeply rooted in their identities and lived experiences within the school community. This approach makes the storybooks both engaging and meaningful, ensuring that all teachers and deaf students feel included and valued in the storytelling process. Additionally, artificial intelligence (AI) was integrated as a collaborative tool, enriching the storytelling process with innovative resources and support for both teachers and deaf students. Findings from the study indicate significant improvements in deaf students’ reading literacy and engagement, as well as in teachers’ pedagogical practices. Thus, this study proposes a replicable framework for creating digital storytelling project by blending teacher–student creativity and AI support, fostering literacy and cultivating a reading culture in schools. By emphasizing identity-driven narratives, the project bridges the gap in reading literacy outcomes, offering a practical and inclusive approach to deaf education.